(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
In this article, the problems of improving pedagogical skills in culture and art education and its innovative solutions are presented. Analytical information was also provided about the reforms implemented in the field of education today, pedagogical skills, and current topics in the educational process